A study of primary mainstream teachers' attitudes towards inclusion of students with special educational needs: a perspective from Dubai - Khan, Lavina (2005)
One of the main challenges facing primary mainstream teachers in Dubai (UAE) stems from the current educational movement towards inclusion. It is an international phenomenon, a process that emphasizes providing special education services to students with special educational needs within the regular classrooms. The purpose of the study was to identify perceptions about educating students with special educational needs in the mainstream education setting. The researcher examines the issue of inclusive education and the attitudes towards inclusion among the primary mainstream teachers in Dubai in the very large private sector. The study was also designed to identify whether these teachers perceived themselves capable of adapting to what inclusion requires. The study relied on qualitative methods. Questionnaires were given to primary mainstream teachers working in two private schools in Dubai. Additionally more teachers were interviewed too. All teachers involved in the study are expatriates. An analysis of data collected indicated that primary mainstream teachers in Dubai in the private sector favour traditional special education service delivery models over full inclusive practices. These teachers felt students with special educational needs lack skills needed to master the mainstream regular classroom course content. The teachers also expressed that the large teaching load in the mainstream classroom makes it hard to meet the needs of students with special educational needs in the private sector. However, results also indicated that teachers perceive additional training, support from administrators and access to related services and resources are necessary in order to meet the needs of their students with special educational needs in the mainstream education setting. The study ended with research based recommendations for future practice.